Chitinase Activity of Some Bacterial Strains Isoiated from Iraqi Soil. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The chltinase aeth·ity of thebacterial isolates were detennfned, and it was found that the isolae S.marcescens HL-165 has the highestacitivity in degradation of crJtin gi...ing ma.'dmumartivity of chitinase (0.894 U ml)-l m the seventh day of inocubation, then the isolate B. Licheniformis ISR~-75 which gave maximum activity (0.486 u ml)-l in the fowih day of inocubation, the isolate B, mycodides CH-45 occpied the thirddegree giving ma.ximum activity (0.346 U ml)-l it, the ninth day of inocubation, whereas the isolate. Streptomyces spp. Act-14 has the lowest activity ghing maximum acthity (0.240 U ml)-l in the twelfth day of inocubation, in colloidal chitin medium.It was found the isolate B. Licheniformis ISR\-"5 prnduced chitinase when grown at 50 C in chitin broth medium whereas ihe other Bad'erial isolates produced this enzYlIle when they grown at (28-30) C i.n the same medium.